Corticosteroids Improve Renal Survival: A Retrospective Analysis From Chinese Patients With Early-Stage IgA Nephropathy - Qin, Aiya; Pei, Gaiqin; Tang, Yi; Tan, Li; Wei, Xingfu; Zhong, Zhengxia; Zhou, Ling; Chen, Changyun; Qin, Wei (Frontiers in Medicine, 2020)
Background: The efficacy and safety of corticosteroids and immunosuppressive therapy remain controversial for the treatment of immunoglobulin A nephropathy (IgAN). This study aimed to evaluate the effects of corticosteroid and immunosuppressant therapy in Chinese patients with early-stage IgAN whose estimated glomerular filtration rate (eGFR) was ≥45 ml/min/1.73 m2 and proteinuria was ≥1 g/24 h at biopsy. Methods: Patients with biopsy-proven IgAN were retrospectively enrolled from four study centers between 2007 and 2016. Patients were regularly followed up for at least 1 year or until the study end point. Patients were categorized into three treatment groups: supportive care (SC), steroids alone (CS), and steroids plus immunosuppressants (IT). The observed responses to therapy included complete remission (CR), partial remission (PR), no response (NR), and end-stage renal disease (ESRD). The primary end point of the current study was defined as a 50% decline in eGFR and/or ESRD. Results: A total of 715 patients (male 47% and female 53%) were recruited and followed up for 44.69 ± 24.13 months. The observed CR rate was 81.8% with corticosteroids alone (CS), 62.7% with corticosteroids + immunosuppresants (IT), and 37% with supportive care alone (SC). Renal outcomes were remarkably better in the CS group compared with the SC and IT groups (the percentage of patients reaching the end point in each group was 4.6 vs. 14.4 vs. 11.5%, respectively; p = 0.001). Moreover, 36 and 80-month renal survival were significantly better for the CS group (98.3 and 86.4%) than for the IT (94.2 and 82.4%) and SC (94.0 and 51.6%) groups. Early CKD stage also presented with better kidney survival (p < 0.001). Renal survival of CKD stage 1 patients was relatively good regardless of the specific treatment regimen. CS and IT treatment significantly improved renal survival for CKD stage 2 patients when compared with the SC group (p < 0.001 and 0.007, respectively). However, renal survival of CKD stage 3a patients was not impacted by any of the three treatment regimens. Subgroup analysis also showed that renal survival of patients with proteinuria >3.5 g, M1, E0, S1, T0, and C0 was significantly better in the CS group than in the SC and IT groups. A multivariate model showed that hypertension, serum creatinine, E1 lesion, and T1/T2 lesion remained independent predictors of poor renal survival. Conclusions: Immunosuppressive therapy does not have further benefit beyond that provided by steroids. Corticosteroids plus optimal supportive care may further be beneficial in treating early-stage IgAN patients in that it could significantly improve the short-term renal outcome.